Persaingan Strategi Politik UMNO Dan PAS Di Malaysia (Dari Wacana Syariat Islam hingga Konsep Islam Hadhari) - Daulay, Hamdan (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The shifts of Islam politics in Malaysia are very interesting to watch and observe, especially the political phenomenon done by UMNO and PAS. UMNO as the ruling party which is Malay-and-Islam-based is competing hard with PAS as the opposition which is also Malay-and-Islam-based. These two parties underwent political shifts as the political dynamics happened in society. UMNO was at first known as a secular party supported by the elite of the party having western education background. In its development, UMNO shifted into a party with many policies that somewhat benefited Malay ethnic and the Muslims. This shift, which benefited the Muslims and Malay ethnic, happened in the era of Mahathir Mohammad.